EDUKASI PENCEGAHAN KANKER PAYUDARA MELALUI TEKNIK SADARI TERHADAP PENINGKATAN PENGETAHUAN DETEKSI DINI KANKER PAYUDARA PADA REMAJA - Rahel Charolina Putri; Yora Nopriani; Bela Purnama Dewi (LPPM STIKes Mitra Adiguna, 2026)
Bre ast cance r i s one of the di se ase s wi th the hi ghe st i nci de nce and mortali ty rate s i n wome n. E arly de te cti on through bre ast se lf-e xami nati on (BSE ) i s i mportant to i ntroduce from adole sce nce as a pre ve nti ve me asure . Thi s study ai ms to de te rmi ne the e ffe ct of bre ast cance r pre ve nti on e ducati on through BSE te chni que s usi ng le afle ts on i ncre asi ng knowle dge of e arly bre ast cance r de te cti on among fe male stude nts at Bi na Ci pta Pale mbang Hi gh School. Thi s study use d a pre -e xpe ri me ntal de si gn wi th a one -group pre te st–postte st approach on 31 fe male stude nts se le cte d usi ng a total sampli ng te chni que . The re se arch i nstrume nt was a knowle dge que sti onnai re . The re sults of uni vari ate analysi s showe d that the ave rage le ve l of knowle dge of re sponde nts be fore be i ng gi ve n he alth e ducati on was 8.06 and i ncre ase d to 12.35 afte r be i ng gi ve n e ducati on, re sulti ng i n an i ncre ase of 4.29. Thi s analysi s i llustrate s an i ncre ase i n knowle dge be fore furthe r te sti ng. The re sults of the Shapi ro–Wi lk te st showe d that the data we re normally di stri bute d, and the Pai re d Sample t-te st analysi s showe d a si gni fi cant di ffe re nce be twe e n be fore and afte r e ducati on (p < 0.05). I t was conclude d that BSE e ducati on usi ng le afle ts had an e ffe ct on i ncre asi ng adole sce nt knowle dge . I t i s re comme nde d that e ducati onal programs be carri e d out conti nuously i n schools as an e ffort to de te ct bre ast cance r e arly.